2008
DOI: 10.1016/j.alcohol.2008.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol exposure during the first two trimesters-equivalent alters the development of corpus callosum projection neurons in the rat

Abstract: Children exposed prenatally to alcohol can display a variety of neural deficits, including an altered development of the corpus callosum (CC), the largest interhemispheric axon pathway in the brain. Furthermore, these children show functional abnormalities that are related to brain regions with significant numbers of CC connections. Little is known about how alcohol imparts influence on CC development, but one possible mechanism is by affecting the corpus callosum projection neurons (CCpn) directly. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Midline callosal hypoplasia was detected in both P0 and P20 PrEE mice, consistent with previous studies in both human and mouse that demonstrate an association between PrEE and shape abnormalities with volumetric changes in the CC (Gautam et al., ; Livy and Elberger, ). Our results show an initial thinning of the CC at birth, lasting through P20, due to PrEE.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Midline callosal hypoplasia was detected in both P0 and P20 PrEE mice, consistent with previous studies in both human and mouse that demonstrate an association between PrEE and shape abnormalities with volumetric changes in the CC (Gautam et al., ; Livy and Elberger, ). Our results show an initial thinning of the CC at birth, lasting through P20, due to PrEE.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have identified noncortical damage to the developing nervous system from PrEE. For example, West and colleagues described abnormal development in the hippocampus, cerebellum, and CC following PrEE in a rat model of FASD (Livy and Elberger, ; Livy et al., ; Maier and West, ).…”
mentioning
confidence: 99%
“…Conventional neuroanatomical methods applied to postmortem human or animal tissue have provided evidence that the ADD changes in neurological conditions such as amyotrophic lateral sclerosis (ALS) (Cluskey and Ramsden, 2001) and multiple sclerosis (MS) (Trapp et al, 1998; Evangelou et al, 2001; Lovas et al, 2000). In addition, several pathologies, including autism (Hughes, 2007), dyslexia (Njiokiktjien et al, 1994), schizophrenia (Randall, 1983), and even alcoholism (Livy and Elberger, 2008), have been associated with changes in the distribution of axon size. Changes in the number of axons and their diameters also take place throughout normal development accompanying the period of dynamic behavioral, cognitive, and emotional changes in childhood and adolescence (Yakovlev, 1967; Pfefferbaum et al, 1994; Gregg et al, 2007; Barnea-Goraly et al, 2005; Schlaug et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted primarily in rodent have reported ethanol-induced impairments in neurogenesis (Goodlett and Horn, 2001), neuronal migration (Aronne et al, 2011) and axonal outgrowth (Granato et al, 2003; Lindsley et al, 2003; Livy and Elberger, 2008). Regarding the latter, low (12.5 mM) concentrations of ethanol impair growth cone responses to guidance cues, including semaphorins and netrins (Sepulveda et al, 2011), known to regulate axonal growth and targeting (Behar et al, 1996; Luo et al, 1995; Serafini et al, 1994; Steup et al, 2000).…”
Section: Introductionmentioning
confidence: 99%